Tradición y erudición en el libro XIII de Deipnosophistai de Ateneo de Náucratis (Minerva, 2019)
Athenaeus of Naucratis did not only transcribe skilfully and learnedly texts written by authors from previous days, but also had a wide knowledge of the literary tradition, which enabled him to create a structurally coherent work belonging to the symposiac genre. Within the work Deipnosophistai, book XIII is a good example of the grammarian's literary achievements. On women is not only a έρωτικός λόγος adapted to the literary demands of his time but also a real encyclopaedia of 'erotic' literature ranging from Homer to the Hellenistic period.